A new species and new synonym of subgenus Chlaeniellus Reitter, 1908 (Coleoptera: Carabidae) with re-establishment of Chlaenius (Chlaeniellus) rapyllii Morvan, 1975 as a valid species - Azadbakhsh, Saeed (Zootaxa, 2017)
A new species of the subgenus Chlaeniellus Reitter, 1908 (Coleoptera: Carabidae), namely Chlaenius (Chlaeniellus) kirschenhoferi sp. n., is described and illustrated from northeast Pakistan. Chlaenius (Chlaeniellus) rapyllii Morvan (1975), is confirmed as a valid species and it is proposed that Chlaenius (Lithochlaenius) asara Kirschenhofer, 2014 is a synonym of Chlaenius (Chlaeniellus) flavipes Menetries, 1832.